Progress in technology advancements for next generation concentrated solar power using solid particle receivers - Muhammad Imran Khan (17346898) (2022)
A global transition towards more sustainable production and consumption systems is underway. This transition processes particularly visible in energy systems, where modern renewables, majorly solar photovoltaic and wind power, accounted for around 10 %iof global power production in 2020. In this context, concentrated solar power technologies are seen to be one of the most promising ways to generate electric power in coming decades. However, due to unstable and intermittent nature of solar energy availability, one of the key factors that determine the development of concentrated solar power technology is the integration of efficient and cost-effective heat transfer fluid and thermal energy storage systems. The current commercial concentrated solar power plants are based Rankine Cycle using steam turbines for converting solar thermal energy into electrical energy. The operating temperature of the steam turbine is limited by the solar salt heat transfer fluid ati565 °C, resulting in a net design point efficiency of 42–45 %. So one of the main challenges for the next-Gen concentrated solar power technologies is the development of alternative heat transfer fluid and thermal energy storage materials with lower costs that could Work at temperatures higher than 565 °C of the current nitrate-based molten salt mixtures. In this context, over the past ten years, interest in solid particle receivers have been proposed to overcome current working temperature limits, since the particle media can be stable for temperatures close to 1000 °C. This paper presents a comprehensive review on solid particle solar receiver technologies for concentrated solar power application and an update of the latest developments of different technologies of particle receiver systems that are commercially available or under investigation. It intends to understand and explain the foundations of the innovative concepts, future research directions and strategies developed over the past 10 years to tune the engineering and thermal sciences of particle receiver systems. Insight into classes of solar particle receiver system with details like their geometrical configurations, design parameters, physical properties, operational issues, cost, technology readiness level, suitability to concentrated solar power application is provided. Other Information Published in: Sustainable Energy Technologies and Assessments License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.seta.2022.102813